2020
DOI: 10.1117/1.jatis.6.4.045005
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront sensing and control in space-based coronagraph instruments using Zernike’s phase-contrast method

Abstract: Future space telescopes with coronagraph instruments will use a wavefront sensor (WFS) to measure and correct for phase errors and stabilize the stellar intensity in high-contrast images. The HabEx and LUVOIR mission concepts baseline a Zernike wavefront sensor (ZWFS), which uses Zernike's phase contrast method to convert phase in the pupil into intensity at the WFS detector. In preparation for these potential future missions, we experimentally demonstrate a ZWFS in a coronagraph instrument on the Decadal Surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…As predicted by the convolutional approach, Figure 3 shows that the sensitivity for a high spatial frequency increases with the dot diameter. This behavior has been discussed briefly in previous literature (Ruane et al 2020) without further analysis. It is here explained thanks to the convolutional model.…”
Section: Impact Of the Dot Diameter On The Zwfs Sensitivitymentioning
confidence: 65%
“…As predicted by the convolutional approach, Figure 3 shows that the sensitivity for a high spatial frequency increases with the dot diameter. This behavior has been discussed briefly in previous literature (Ruane et al 2020) without further analysis. It is here explained thanks to the convolutional model.…”
Section: Impact Of the Dot Diameter On The Zwfs Sensitivitymentioning
confidence: 65%
“…Also, more realistic telescope apertures and coronagraphs, such as the standard Lyot coronagraph and Vector Vortex Coronagraph (Mawet et al 2009), need to be included. Furthermore, recent studies have shown that there are also limitations coming from DM(s) location(s) as well as DM actuator number and quantization errors (Beaulieu et al 2017(Beaulieu et al , 2020Ruane et al 2020). Therefore, we need to add more realistic DM models in future simulations.…”
Section: Discussionmentioning
confidence: 99%
“…This in-situ ZWFS has been shown to be sensitive to picometer-level wavefront variations. 16 For the sake of simplicity, our simulation effectively assumes an ideal in-band ZWFS that collects all the light passing through the 20% bandwidth visible filter. In reality, the ZWFS would operate in a different band than science observation's filter, but this distinction is not relevant to our analysis.…”
Section: Wavefront Sensing and Control Architecturementioning
confidence: 99%
“…17 Here, we round β to one at each wavelength and spatial frequency in a Fourier basis, while β has recently been derived more precisely considering the realistic diffraction from the focal plane mask. 16 We generalize the calculation to a random orthonormal basis in section 3.3. Our assumed telescope and WFS parameters are summarized in Table 1.…”
Section: Wavefront Sensing and Control Architecturementioning
confidence: 99%